Methods of testing plastics. Thermoplastics pipes, fittings and valves. Plastics pipes and fittings. Preparation of polyethylene (PE) pipe/pipe or pipe/fitting test piece assemblies by butt fusion Part 11, (15th February 1998) - British Standards Institution,
No abstract available